2009
DOI: 10.1088/0067-0049/183/1/17
|View full text |Cite
|
Sign up to set email alerts
|

THE FIFTH DATA RELEASE SLOAN DIGITAL SKY SURVEY/ XMM-NEWTON QUASAR SURVEY

Abstract: We present a catalog of 792 DR5 SDSS quasars with optical spectra that have been observed serendipitously in the X-rays with the XMM-Newton. These quasars cover a redshift range of z = 0.11 -5.41 and a magnitude range of i = 15.3-20.7. Substantial numbers of radio-loud (70) and broad absorption line (51) quasars exist within this sample. Significant X-ray detections at ≥ 2σ account for 87% of the sample (685 quasars), and 473 quasars are detected at ≥ 6σ, sufficient to allow X-ray spectral fits. For detected s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
53
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 102 publications
(130 reference statements)
11
53
0
Order By: Relevance
“…Because the errors on the photon index are not symmetric, we used the average value for the individual errors in each case. We obtain a mean value of Γ = 2.05 ± 0.03 with an intrinsic dispersion of σ = 0.26 ± 0.02 for the BSS and Γ = 1.98 ± 0.08 with an intrinsic dispersion of σ = 0.29 ± 0.05 for the HBSS, in agreement with previous works (Mateos et al 2010;Young et al 2009;Dadina 2008;Mainieri et al 2007;Page et al 2006;Mateos et al 2005a,b). Errors were extracted from the 1σ confidence contours.…”
Section: Photon Indexsupporting
confidence: 92%
See 1 more Smart Citation
“…Because the errors on the photon index are not symmetric, we used the average value for the individual errors in each case. We obtain a mean value of Γ = 2.05 ± 0.03 with an intrinsic dispersion of σ = 0.26 ± 0.02 for the BSS and Γ = 1.98 ± 0.08 with an intrinsic dispersion of σ = 0.29 ± 0.05 for the HBSS, in agreement with previous works (Mateos et al 2010;Young et al 2009;Dadina 2008;Mainieri et al 2007;Page et al 2006;Mateos et al 2005a,b). Errors were extracted from the 1σ confidence contours.…”
Section: Photon Indexsupporting
confidence: 92%
“…An anti-correlation between the photon index and the X-ray luminosity has been recently reported by Green et al (2009) and Young et al (2009), whereas Saez et al (2008) found a "positive" correlation. It has to be noted that Saez et al (2008) took into account type 1 and type 2 AGN at the same time, the latter being more numerous than the former, whereas we here only considered type 1 AGN.…”
Section: Discussionmentioning
confidence: 82%
“…These values are in excellent agreement with recent measurements of the mean photon index and intrinsic dispersion for type-1 AGN found in the literature (e.g. Young et al 2009;Dadina 2008;Mainieri et al 2007;Page et al 2006;Mateos et al 2005a,b). We note that hard X-ray selected samples ( > ∼ 20 keV) from the INTEGRAL and Swift satellites report marginally flatter spectral slopes for bright type-1 AGN, Γ ∼ 1.7−1.8 (Molina et al 2009;Winter et al 2009;Panessa et al 2008).…”
Section: The Broad Band X-ray Continuumsupporting
confidence: 92%
“…Various studies of the X-ray photon index have produced different results. Some authors claim an anti-correlation between the spectral photon index Γ and the X-ray luminosity (Young et al 2009;Saez et al 2008;Page et al 2005) while other studies suggest the opposite correlation (Dai et al 2004) or no correlation at all (Winter et al 2009;Mateos et al 2005b;George et al 2000;Reeves & Turner 2000). Studies of the X-ray spectra of AGN have generally shown no clear dependence of the AGN X-ray properties on the redshift (Mateos et al 2005a), although some exceptions have been found (Kelly et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These studies, based on Einstein observations, found a mean value of α ox in the range 1.3−1.45. Subsequently, many investigations have been performed (e.g., Yuan et al 1998;Vignali et al 2003;Strateva et al 2005;Steffen et al 2006, hereafter S06;Just et al 2007, hereafter J07; Kelly et al 2008;Green et al 2009;Young et al 2009) which were mainly based on AGN samples selected from the Sloan Digital Sky Survey (SDSS). Most of the previous studies on the relationship between α ox , luminosity and redshift A&A 512, A34 (2010) were based on large samples of optically selected type 1 AGN with a high fraction of X-ray detections.…”
Section: Introductionmentioning
confidence: 99%